Legal Protection for Children as Victims of the Crime of Sexual Intercourse - Firda Salam; Lisnawati W. Badu; Jufryanto Puluhulawa (Universitas Negeri Gorontalo, 2022)
This study aims to determinelegal protection for children as victims of the crime of sexual intercourse.The method used in this research is empirical research methodology. This study uses a qualitative approach and sampling using purposive sampling and using descriptive qualitative analysis techniques. The results of this study indicate thatLegal protection for child victims of the crime of sexual intercourse is given with the aim of protecting victims, especially victims of sexual intercourse in order to get their rights as victims by way of children getting health services as an effort to restore the condition of children as victims of sexual intercourse, children also get legal protection in terms of legal aid, rehabilitation, and prevention. The need for a fair criminal law settlement for victims of sexual intercourse, which adds or considers the rights of victims of sexual intercourse and parents should participate in efforts to provide protection for children by fulfilling children's rights, protecting the best interests of children, and increasing supervision over children. environment and children's play area.